Analysis of Wound Treatment in Patients with Diabetic Foot Ulcer (DFU) Using Honey and Aloe Vera Extracts - Sutrisno, Sutrisno; Yuan Mandira Wicaksana; Atik Setiawan Wahyuningsih (Kirana Publisher (KNPub), 2024)
Diabetic Foot Ulcer (DFU) is a complication of Diabetes Mellitus which occurs due to high blood sugar levels. Treatment for DFU can involve treating pressure sores and mobility exercises and using herbal dressings such as honey and aloe vera extracts. This study aims to analyze the effect of wound care using honey and aloe vera extract on DFU wounds. This research design uses pre-experimental. Data collection used the Bates-Jensen Wound Assessment Tool (BWAT) questionnaire. Analysis used Paired Test. The population used patients with Diabetic Foot Ulcer (DFU) and a sample of 17 respondents was obtained. The results of the study showed that before the wound was treated, the condition of the wound was in the non-regenerating category. After the wound was treated and evaluated, the mean value decreased from previously 25.24 to 16.76. The Paired Test results obtained a Sig value (2-tailed)=0.000 which means it is smaller than α 0.05, thus H1 is accepted. The percentage of influence on wound development was 82.4% indicating that there was regeneration in the wound and 17.6% did not regenerate.